The Efficacy of Proximal Lumbar Curve Flexibility in Patients with Main Thoracic Adolescent Idiopathic Scoliosis Treated by Selective Thoracic Fusion Surgery - Na, Ki-Ho (Korean Society of Spine Surgery, 2010)
STUDY DESIGN: Retrospective radiographic study. PURPOSE: To evaluate the efficacy of the proximal lumbar curve flexibility compared with the traditional whole lumbar curve flexibility in patients with main thoracic adolescent idiopathic scoliosis (MT-AIS). OVERVIEW OF LITERATURE: Traditionally the flexibility of the whole lumbar curve was measured, and the flexibility of the proximal lumbar curve was not analyzed in any study. METHODS: Twenty-eight MT-AIS patients treated by anterior selective thoracic fusion (STF) were evaluated after mean follow-up of 50.1 months (range, 25 to 116 months). The male : female ratio was in 5 : 23. The man age at surgery was 14 years and 8 months (range, 11.4 to 18.4 years). The lumbar curve was divided into the proximal and distal curves by the lumbar apex. RESULTS: The mean final correction rates (CR)/(flexibilities) of the MT, lumbar, proximal lumbar, and distal lumbar curves were 65.2%/(50.5%), 61.9%/(92.8%), 65.3%/(90.9%), and 36.4%/(134%), respectively. With the final lumbar CR, the lumbar flexibility (r = 0.267, p > 0.05) and the proximal lumbar flexibility (r = 0.327, p > 0.05) was similarly correlated. The mean lumbar CR was similar to the proximal lumbar CR (61.9% vs. 65.3%, p = 0.305). And the correlation between the flexibility and the CR was significant only in the proximal lumbar curve (r = 0.457, p < 0.05), but not in the lumbar curve (r = 0.267, p > 0.05) or the distal lumbar curve (r = 0.175, p > 0.05). CONCLUSIONS: The proximal lumbar curve flexibility may be an alternative method of measuring the lumbar flexibility in MT-AIS patients treated by STF.